2012
DOI: 10.5755/j01.ee.23.1.1221
|View full text |Cite
|
Sign up to set email alerts
|

Comovement Dynamics between Central and Eastern European and Developed European Stock Markets during European Integration and Amid Financial Crises – A Wavelet Analysis

Abstract: Stock market comovements between developed (represented in the article by markets of Austria, France, Germany, and the UK) and developing stock markets (represented here by three Central and Eastern European (CEE) markets of Slovenia, the Czech Republic, and Hungary) are of great importance for the financial decisions of international investors. From the point of view of portfolio diversification, short-term investors are more interested in the comovements of stock returns at higher frequencies (short-term mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 39 publications
(53 reference statements)
2
18
0
Order By: Relevance
“…The accession to the European Union has strengthened the linkage. Dajcman, Festic and Kavkler [12] showed that the Central and Eastern European (CEE) stock markets exhibited a lower degree of comovement between themselves and were less interdependent than European stock markets in the developed countries (France, the UK, Germany and Austria). Kizys and Pierdzioch [13] reported that long-run linkages between stock markets in CEE countries and the U.S. stock market intensified in both fundamentals and speculative bubbles during the financial crisis in 2008.…”
Section: Literature Surveymentioning
confidence: 99%
“…The accession to the European Union has strengthened the linkage. Dajcman, Festic and Kavkler [12] showed that the Central and Eastern European (CEE) stock markets exhibited a lower degree of comovement between themselves and were less interdependent than European stock markets in the developed countries (France, the UK, Germany and Austria). Kizys and Pierdzioch [13] reported that long-run linkages between stock markets in CEE countries and the U.S. stock market intensified in both fundamentals and speculative bubbles during the financial crisis in 2008.…”
Section: Literature Surveymentioning
confidence: 99%
“…Such political risk is included as a direct cost. Dajcman et al (2012) investigated the dynamics of stock market return comovements between individual Central and Eastern European countries and developed European stock markets in the period from 1997-2010. They analysed the time-varying dynamics of stock market comovements on a scale-by-scale basis, and they examined how major events (financial crises in the investigated time period and entrance to the European Union) affected the comovement of CEE stock markets with developed European stock markets.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Other studies have used spectral and time-frequency analysis to assess CEE stock market comovements. Dajcman et al (2012), for instance, investigated the co-movements between developed and CEE stock markets in a wavelet framework, finding that the developed M a n u s c r i p t 7 European stock markets were more interdependent in the period under observation than the CEE stock markets. Using cross-wavelet analysis and high-frequency data, Barunik and Vacha (2013) found that CEE market connectedness to the leading market of the region was significantly lower at higher frequencies (in the short run), thus proving the absence of contagion.…”
Section: Demian (2011) Investigated the Impact Of European Union Accementioning
confidence: 99%